Dialogues: with Prof. Dr. Abdellatif Bouazizi President of Ez-zitouna University - Eriouiche, Mohammed; Abdul Latif, Yahya (Nama Journal of Islamic Sciences and Humanities, 2023)
Dialogues: with Prof. Dr. Abdellatif Bouazizi President of Ez-zitouna University